RELATIONSHIP BETWEEN STRESS LEVEL AND COPING MECHANISM WITH PARENT’S ABILITY TO CARE FOR AUTIS CHILDREN - Dwi Iswanti; Dera Alfiyanti; Erna Sulistyawati (Universitas Karya Husada Semarang, 2025)
Introduction: The incidence of autism in Indonesia has increased by 0.15% per year, this affects the level of stress and coping mechanisms of parents of autistic children because they have to take care of children who are very active, angry and difficult to understand the needs of this affects the ability of parents to care for autistic children. Objective: Analyzing the relationship between stress levels and coping mechanisms with parent’s ability to care for autistic children. Methods: This type of descriptive correlation with a cross-sectional approach. The population includes all parents of autistic children in SLB Bina Anggita Special Autism Magelang City. The sample taken in this study were all guardians of autistic with a total of 60 people. The instruments used are the Percevied Stress Scale, Brief Cope, and a questionnaire sheet of parents' ability to care for autistic children. The analysis used in this research is correlation test using Spearman Rank test. Result: There was no correlation between the level of stress and the ability of parents to care for autistic children (p-value = 0.445) and there was a relationship between coping mechanisms and the ability of parents to care for autistic children with a value (p-value = 0.008). Conclusion: All the parents of autistic children in SLB Bina Anggita Magelang City are able to care for autistic children well.